A Lexical Analysis of Two Online Media Articles with regard to Prabowo’s Proposal to end Conflict of Russia and Ukraine - Siti Sopiah; Edi Purnama (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
This study investigated two articles concerning the issue of Prabowo’s proposal to end conflict of Russia and Ukraine published in Sindonews.com and Tribunnews.com. It focusses on two problems, how Prabowo proposal is represented  and what agenda behind such representation. The articles are selected purposively on the basis of specifically. The data analysis is conducted by employing CDA framework that is lexical analysis. It found that Tribunnews.com  tends to represent Prabowo proposal negatively. On the other hands, Sindonews.com potrays Prabowo proposal positively. Those representations lead to an interpretation that parties behind Tribunnews seems to be unsupportive to Prabowo meanwhile Sindonews.com is supportive for Prabowo especially in terms of President election.